(untitled) (Journal of Social Sciences Review, 2022)
Proficient academic writing skill is the need by students of higher education levels to acquire academic success. Therefore, enhancing one’s English language skills, particularly academic writing at the undergraduate level, is crucial for academic success in Pakistani universities. The most significant difficulty, on the other hand, is related to the level of academic writing proficiency exhibited by college-level students. As a result, this study was undertaken using a quantitative technique to evaluate students’ opinions of problematic and tough areas of academic writing skills and to provide recommendations based on them. All enrolled students at public universities in Sindh were included in the study population, and 372 students were chosen using purposive sampling to participate in this study. The research was carried out utilizing a descriptive survey research approach, with questionnaires serving as the major data collection tool. The study’s findings revealed that students struggle with reviewing, summarizing and synthesizing passages, commenting, constructing sentences, paraphrasing, cohesion between paragraphs and sentences, and grammatical issues. Based on these data, it is vital for teachers to take into consideration students’ writing issues, and the explanation of extra writing sessions is among the pedagogical implications.